Transient and lineage-restricted requirement of Ebf3 for sternum ossification - Kuriki, Mao (Development, 2020)
Osteoblasts arise from bone-surrounding connective tissue containing tenocytes and fibroblasts. Lineages of these cell populations and mechanisms of their differentiation are not well understood. Screening enhancer-trap lines of zebrafish allowed us to identify Ebf3 as a transcription factor marking tenocytes and connective tissue cells in skeletal muscle of embryos. Knockout of Ebf3 in mice had no effect on chondrogenesis but led to sternum ossification defects as a result of defective generation of Runx2(+) pre-osteoblasts. Conditional and temporal Ebf3 knockout mice revealed requirements of Ebf3 in the lateral plate mesenchyme cells (LPMs), especially in tendon/muscle connective tissue cells, and a stage-specific Ebf3 requirement at embryonic day 9.5-10.5. Upregulated expression of connective tissue markers, such as Egr1/2 and Osr1, increased number of Islet1(+) mesenchyme cells, and downregulation of gene expression of the Runx2 regulator Shox2 in Ebf3-deleted thoracic LPMs suggest crucial roles of Ebf3 in the onset of lateral plate mesoderm differentiation towards osteoblasts forming sternum tissues.